Impact of T-cell costimulation modulation in patients with undifferentiated inflammatory arthritis or very early rheumatoid arthritis: a clinical and imaging study of abatacept (the ADJUST trial). Issue 3 (23rd November 2009) - Emery, P; Durez, P; Dougados, M; Legerton, C W; Becker, J-C; Vratsanos, G; Genant, H K; Peterfy, C; Mitra, P; Overfield, S; Qi, K; Westhovens, R
Abstract : Background: Several agents provide treatment for established rheumatoid arthritis (RA), but a crucial therapeutic goal is to delay/prevent progression of undifferentiated arthritis (UA) or very early RA. Objective: To determine the impact of T-cell costimulation modulation in patients with UA or very early RA. Methods: In this double-blind, phase II, placebocontrolled, 2-year study, anti-cyclic citrullinated peptide (CCP)2-positive patients with UA (not fulfilling the ACR criteria for RA) and clinical synovitis of two or more joints were randomised to abatacept (∼10 mg/kg) or placebo for 6 months; the study drug was then terminated. The primary end point was development of RA (by ACR criteria) at year 1. Patients were monitored by radiography, MRI, CCP2, rheumatoid factor and 28 joint count Disease Activity Score (DAS28) over 2 years. Results: At year 1, 12/26 (46%) abatacept-treated versus 16/24 (67%) placebo-treated patients developed RA (difference (95% CI) −20.5% (−47.4% to 7.8%)). Adjusted mean changes from baseline to year 1 in Genant-modified Sharp radiographic scores for abatacepttreated versus placebo-treated patients, respectively, were 0 versus 1.1 for total score, and 0 versus 0.9 for erosion score. Mean changes from baseline to year 1 in MRI erosion, osteitis and synovitis scores were 0, 0.2 and 0.2, respectively, versus 5.0, 6.7 and 2.3 in the abatacept versus placebo groups. Safety was comparable between groups; serious adverse events occurred in one patient (3.6%) in each group. Conclusion: Abatacept delayed progression of UA/very early RA in some patients. An impact on radiographic and MRI inhibition was seen, which was maintained for 6 months after treatment stopped. This suggests that it is possible to alter the progression of RA by modulating T-cell responses at a very early stage of disease. Trial registration number: NCT00124449.